Estimation of the monthly average global and diffuse solar radiation for the city Bareilly, Uttar Pradesh, India - Akanksha Varshney; K. Namrata; Bhushan Mahajan (Carbon: Science and Technology, 2018)
This paper presents a process to develop the monthly global and diffused solar radiation data for the city Bareilly, Uttar Pradesh in order to exploit the solar energy available at the location throughout the year. It is located in the northern zone of Uttar Pradesh at 28.367°N latitude and 79.4304°E longitude at an elevation of 268 meters. The values of monthly average global solar radiation are calculated using the regression constants in the model provided by Gopinathan. Kreith and Gupta model has been used for estimating the values of monthly average diffuse solar radiation. The calculated data has been analyzed and the result has been simulated through matlab.